Sustained Self-Regulation of Energy Intake: Initial Hunger Improves Insulin Sensitivity - Mario Ciampolini; David Lovell-Smith; Riccardo Bianchi; Boudewijn de Pont; Massimiliano Sifone; Martine van Weeren; Willem de Hahn; Lorenzo Borselli; Angelo Pietrobelli (Journal of Nutrition and Metabolism)
Background. Excessive energy intake has been implicated in diabetes, hypertension, coronary artery disease, and obesity. Dietary restraint has been unsuccessful as a method for the self-regulation of eating. Recognition of initial hunger (IH) is easily learned, can be validated by associated blood glucose (BG) concentration, and may improve insulin sensitivity. Objective. To investigate whether the initial hunger meal pattern (IHMP) is associated with improved insulin sensitivity over a 5-month period. Methods. Subjects were trained to recognize and validate sensations of IH, then adjust food intake so that initial hunger was present pre-meal at each meal time (IHMP). The purpose was to provide meal-by-meal subjective feedback for self-regulation of food intake. In a randomised trial, we measured blood glucose and calculated insulin sensitivity in 89 trained adults and 31 not-trained controls, before training in the IHMP and 5 months after training. Results. In trained subjects, significant decreases were found in insulin sensitivity index, insulin and BG peaks, glycated haemoglobin, mean pre-meal BG, standard deviation of diary BG (BG as recorded by subjects' 7-day diary), energy intake, BMI, and body weight when compared to control subjects. Conclusion. The IHMP improved insulin sensitivity and other cardiovascular risk factors over a 5-month period.